Institutional Sustainability of a Community Conservation Agreement in Lore Lindu National Park - Massiri, Sudirman Daeng; Nugroho, Bramasto; Kartodihardjo, Hariadi; Soekmadi, Rinekso (Forestry Faculty, Universitas Hasanuddin, 2019)
The arrangement of self-governance institutions is the main obstacle to achieving sustainability for ecosystems and local livelihoods. The aim of this study was to describe the institutional sustainability of Community Conservation Agreement (CCA) in Lore Lindu National Park (LLNP), located in Central Sulawesi Province, Indonesia. This study applied a descriptive method by identifying and analyzing the relationship between characteristics of the community and nearby resources, as well as the regulations and rules (formal and local rules arranged in CCA), behavior and performance of institutional CCA, and the interests and power of stakeholders. The research demonstrates that high institutional sustainability of CCA is not only determined by the relations among the community, but that it is also motivated by the common interests to preserve water in the LLNP area as a means for avoiding disaster. However, principles of collective-choice arrangements, minimal recognition of rights to organize, and nested enterprises in CCA were not running well. Strategies to improve the institutional sustainability of CCA include unifying landscape zones that describe property rights of local communities within a conservation area that is recognized by all stakeholders and should be supported by formal legal rules.